Regionalism in the organisation of traffic in Hungary - Bói, Loránd (Acta Agraria Debreceniensis, 2012)
In the member states of the European Union, especially in Germany and Austria, regionalism has a growing importance by the organising of public services. At the field of public transport services the regional organising methods will be realised through the establishment of public transport associations in interest of coordinating the local, suburban and regional public transport interests. In the period since the 90’s there are a not a lot of best practices regarding the regional organisation of public transport services in Hungary. The study goals to present the position of the local and regional interest in the public transport organisation in Hungary, and deals with the reason the lack of best practices also.